Peningkatan Hasil Belajar PAI Siswa Kelas X Melalui Implementasi Ekstrakurikuler Kepesantrenan di SMA 'Aisyiyah Boarding School - Rayhan Rizky Agam Gaeno; Mochamad Fadlani Salam; Sitti Chadidjah; Iim Ibrohim; Mukhlishah Mukhlishah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2026)
Islamic Religious Education (PAI) plays a vital role in shaping students' character and knowledge. The limitation of PAI teaching hours in public schools is addressed by SMA ‘Aisyiyah Boarding School through kepesantrenan (Islamic boarding school-style) extracurricular activities, which include habitual worship and religious learning. This study aims to analyze the implementation of these activities, the PAI learning outcomes of Class X students, and their impact on improving learning outcomes. The research used a qualitative approach with a case study method, based on B.F. Skinner's behaviorism theory. Data were collected through observation, interviews (PAI teachers, extracurricular teachers, students, principal), and documentation studies (PAI scores). Data analysis followed the Miles and Huberman model, verified through triangulation. The findings show: First, the implementation uses a behavioristic approach through structured activities, rewards, and positive discipline, successfully forming religious habits; Second, students' PAI learning outcomes improved, covering cognitive material mastery, affective value internalization, and psychomotor worship independence; Third, kepesantrenan extracurricular activities are proven to enhance PAI learning outcomes by creating a holistic learning environment that facilitates the understanding of PAI material.